A Review of Virtual Machine Attack Based on Xen - Ren xun-yi; Zhou yu-qi (MATEC Web of Conferences, 2016)
Virtualization technology as the foundation of cloud computing gets more and more attention because the cloud computing has been widely used. Analyzing the threat with the security of virtual machine and summarizing attack about virtual machine based on XEN to predict visible security hidden recently. Base on this paper can provide a reference for the further research on the security of virtual machine.